Distributed activation energy model for lignocellulosic biomass torrefaction kinetics with combined heating program. (15th January 2022) - Feng, Yipeng; Qiu, Keying; Zhang, Zhiping; Li, Chong; Rahman, Md. Maksudur; Cai, Junmeng
Abstract: Torrefaction kinetics is fundamental for the theoretical investigation and industrial application of torrefaction processes. Most of biomass torrefaction kinetic studies focused on kinetic modelling under either isothermal or linear heating programs with one or several activation energies, which couldn't accurately reflect its reaction mechanisms. A distributed activation energy model (DAEM) was proposed to analyze logging residue torrefaction kinetics with a combined heating program at different temperatures. The model parameters were efficiently optimized by using the pattern search method. The results showed that the DAEM could excellently describe the experimental data of logging residue torrefaction at various conditions. The obtained activation energy distributions for logging residue torrefaction with the combined heating program at final temperatures of 240, 270 and 300 °C lay in the range of 154–172 kJ mol −1, 160–177 kJ mol −1 and 165–185 kJ mol −1, respectively. These findings indicated that major reactions occurring during torrefaction were the devolatilization and carbonization of biomass's hemicellulose constituents and partial decomposition of biomass's cellulose constituents. The experimental kinetic data of mesocarp fiber torrefaction at final temperatures of 220, 250 and 270 °C from the literature was also successfully described by the DAEM. Graphical abstract: Image 1 Highlights: DAEM excellently describes lignocellulosic biomass torrefaction kinetics. Activation energy distributions for biomass torrefaction were obtained. Major reactions of biomass torrefaction are hemicellulose decomposition.